IDENTIFIKASI PENGARUH TAKARAN BAHAN DASAR TERHADAP KUALITAS MIE BASAH BERDASARKAN DAYA SERAP AIR DAN METODE DOE - Anis Siti Nurrohkayati; Binyamin Binyamin; Muhammad Khairul (Jurnal Ilmiah Manuntung, 2020)
Wet noodles are one of the foods that are favored by all people, especially in Indonesia. Wet noodles are made from basic ingredients of wheat flour or wheat flour. So far there have been many innovations of wet noodles with basic ingredients apart from wheat flour. The difference in the basic ingredients and additional ingredients can affect the quality of the noodles. However, it is not yet known whether the effect of the quality of the wet noodles is influenced by the type of flour used, the amount of the basic ingredients, or whether there is an effect of the extracts of other ingredients on the quality of the wet noodles. This is the reason for this research. Thus, this study aims to determine the types and differences in the use of basic ingredients in making wet noodles that can affect the quality of wet noodles. Measurement parameters used are by calculating the level of water absorption. The combination of wheat flour, cassava flour, and seaweed were used in this study. Calculation analysis is performed using the Taguchi method. The Taguchi method is the methodology in the world of Engineering which can be used as a method to measure or improve the quality of a product, as well as minimize costs. Wet noodle making experiments were conducted according to the Taguchi Design of Experiments (DOE) method. The repetition of the experiment was carried out eight times according to the orthogonal array (OA) matrix used. There are 5 control factors and 3 noise factors that are used in this study. Control factors are wheat flour, cassava flour, eggs, salt, and seaweed. Meanwhile, the noise factor is a lot of water, a long time to rest dough, and a long time to steam. ANOVA analysis and mean effect were carried out to find out which factors had the most significant influence on the quality of the noodles.